2019
DOI: 10.1097/aln.0000000000002661
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Tube Effects on Breathing during Sedation for Dental Procedures

Abstract: Background: Intravenous sedation is effective in patients undergoing dental procedures, but fatal hypoxemic events have been documented. It was hypothesized that abnormal breathing events occur frequently and are underdetected by pulse oximetry during sedation for dental procedures (primary hypothesis) and that insertion of a small-diameter nasopharyngeal tube reduces the frequency of the abnormal breathing events (secondary hypothesis). Methods: In this nonblinded randomized control study, frequency of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Anaesthesiologist have an important role in screening of the patients, the early recognition of OSA, and caring for a patent upper airway during deeper sedation procedures. 72 Patients with OSA present with oxidative stress and systemic inflammation. 73,74 Periodontal disease shares some of these mechanisms, and recent studies have shown a significant association with OSA.…”
Section: Dentist's Role In Obstructive Sleep Apnoeamentioning
confidence: 99%
See 1 more Smart Citation
“…Anaesthesiologist have an important role in screening of the patients, the early recognition of OSA, and caring for a patent upper airway during deeper sedation procedures. 72 Patients with OSA present with oxidative stress and systemic inflammation. 73,74 Periodontal disease shares some of these mechanisms, and recent studies have shown a significant association with OSA.…”
Section: Dentist's Role In Obstructive Sleep Apnoeamentioning
confidence: 99%
“…Dental anaesthesiology is linked to OSA, because OSA patients are often prone to increased risk of complications during deeper sedation. Anaesthesiologist have an important role in screening of the patients, the early recognition of OSA, and caring for a patent upper airway during deeper sedation procedures 72 …”
Section: Obstructive Sleep Apnoea: the Dentist's Rolementioning
confidence: 99%
“…Pharmacological sedation is becoming frequently used in various clinical situations such as invasive endoscopy, minor surgery, radiological examinations for children, and mechanical ventilation in ICU [10,25,26,27]. Apneas and hypopneas during sedation were spontaneously terminated either with or without cortical arousal in our patients.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, deaths in patients undergoing GI endoscopy during and after propofol sedation have been reported [19]. Clearly, future studies need to explore clinical significance of the non-hypoxemic respiratory disturbances and roles of the respiratory monitoring such as capnography, nasal pressure, snoring sound measurement during sedation [25,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…will be informed of the allocation of the participant immediately before the initiation of intravenous sedation to reduce potential bias. The anesthesiologist will provide conscious intravenous sedation by a bolus intravenous injection of midazolam (1 to 3 mg) and propofol (5 to 10 mg), followed by continuous infusions of propofol (1 to 3 mg kg −1 h −1 ) using the target-controlled infusion system [19,20]. After an acclimatization period for TPR (30 s), a baseline evaluation (i.e., no control of tongue position with TPR in place) will be performed (1 min) (Figure 4).…”
Section: Study Protocolmentioning
confidence: 99%